Remodeling of Stromal Cells and Immune Landscape in Microenvironment During Tumor Progression - Arora, Leena; Pal, Durba (Frontiers in Oncology, 2021)
The molecular understanding of carcinogenesis and tumor progression rests in intra and inter-tumoral heterogeneity. Solid tumors confined with vast diversity of genetic abnormalities, epigenetic modifications, and environmental cues that differ at each stage from tumor initiation, progression, and metastasis. Complexity within tumors studied by conventional molecular techniques fails to identify different subclasses in stromal and immune cells in individuals and that affects immunotherapies. Here we focus on diversity of stromal cell population and immune inhabitants, whose subtypes create the complexity of tumor microenvironment (TME), leading primary tumors towards advanced-stage cancers. Recent advances in single-cell sequencing (epitope profiling) approach circumscribes phenotypic markers, molecular pathways, and evolutionary trajectories of an individual cell. We discussed the current knowledge of stromal and immune cell subclasses at different stages of cancer development with the regulatory role of non-coding RNAs. Finally, we reported the current therapeutic options in immunotherapies, advances in therapies targeting heterogeneity, and possible outcomes.